GVCs in Central Europe : a perspective of the automotive sector after COVID-19 - Černá, Iveta, 1979-; Éltetö, Andrea, 1969-; Folfas, Paweł; Kuźnar, Andżelika; Křenková, Eva; Minárik, Marek; Przeździecka, Eliza; Szalavetz, Andrea; Túry, Gábor; Zábojník, Stanislav (Bratislava : Vydavatel'stvo Ekonóm, 2022)
This scientific monograph is a joint output of more than a year of cooperation among the researchers from SGH Warsaw School of Economics, University of Economics in Bratislava (EUBA), Prague University of Economics and Business (VŠE), and the Centre for Economic and Regional Studies (CERS) in global value chains research in the automotive industry, emphasizing the value added importance in international business, particularly in the time of the COVID-19 pandemic impact. The authors hereby wish to express gratitude to the Visegrad Fund for financial support of the outputs within the project. They would also like to thank the reviewers for their valuable comments and experts from practice who participated in the questionnaires and structured interviews and colleagues and students who contributed to implementing the project outputs.
Vědecká monografie analyzuje postavení zemí střední Evropy v globálních hodnotových řetězcích (Global Value Chains – GVCs) se zaměřením na automobilový průmysl v období po pandemii COVID-19. Autoři z výzkumných institucí Polska, Slovenska, České republiky a Maďarska zkoumají význam přidané hodnoty v mezinárodním podnikání, strukturální změny v produkčních sítích a dopady pandemické krize na fungování a odolnost dodavatelských řetězců.
Obsahuje bibliografické odkazy
Keywords: 2019-2020; 1995-2020; mezinárodní podnikání; ekonomická přidaná hodnota; logistika (management); výrobní management; automobilový průmysl; země Visegrádské skupiny; srovnávací studie; international business; economic value added; business logistics; production management; automobile industry; Visegrád Group countries; comparative studies